IMPLEMENTATION OF MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT - Sumitra Putri Dewi, Rini Hendrita (Inovasi Pendidikan, 2021)
This research is about the implementation of mind mapping technique to improve students reading comprehension in descriptive text at grade VIII SMP N 1 Sintuk Toboh Gadang. This research was classified as pre-experimental research. The subjects of this research were 32 students of class VIII-1 of SMP N 1 Sintuk Toboh Gadang. The data was quantitative data taken from pre-test and post-test. The result of this research  showed that the implementation of mind mapping technique on teaching reading was effective. It can be seen in the pre-test and post-test score. The pre-test mean is 50,93 and the post-test mean is 83,44. If it reviewed from tcount and ttable withα is 0,05. It means tcount is higher than ttable  (-21,8237 2,039). Based on the data, it can be concluded that mind mapping technique is appropriate to be applied in teaching reading comprehension, particularly at grade VIII SMP N 1 Sintuk Toboh Gadang.